2022
DOI: 10.3390/en15020596
|View full text |Cite
|
Sign up to set email alerts
|

Communicating the Values and Benefits of Home Solar Prosumerism

Abstract: Clearly and accurately communicating the economic, environmental, and social benefits of solar PV prosumerism poses significant challenges. Previous research shows that government policies and public engagement campaigns can positively impact solar prosumerism; however, little is known about the quality and accuracy of information exchanged between rooftop solar installers and potential prosumers. This study addresses part of this gap with a mixed methods approach. First, a multimodal discourse analysis of ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…This is a development opportunity for a given community, e.g., living in rural areas [48], although this solution is not without certain risks. In a more detailed approach, the differences in the behavior of active recipients are also analyzed depending on the specificity of renewable energy sources (i.e., solar, wind, and bioenergy installations) [49] and depending on the methods of communicating the benefits achieved by individual recipients generating solar energy for their own needs [50]. The latter of the above-mentioned trends includes the research conducted by Junlakarn, Kokchang and Audomvongseree [51] on the trade in green energy between recipients via an Internet platform and the research carried out by Drabecki and Toczyłowski [52] relating to the interest of active recipients in optimizing not only the financial costs of energy, but also social and environmental costs, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is a development opportunity for a given community, e.g., living in rural areas [48], although this solution is not without certain risks. In a more detailed approach, the differences in the behavior of active recipients are also analyzed depending on the specificity of renewable energy sources (i.e., solar, wind, and bioenergy installations) [49] and depending on the methods of communicating the benefits achieved by individual recipients generating solar energy for their own needs [50]. The latter of the above-mentioned trends includes the research conducted by Junlakarn, Kokchang and Audomvongseree [51] on the trade in green energy between recipients via an Internet platform and the research carried out by Drabecki and Toczyłowski [52] relating to the interest of active recipients in optimizing not only the financial costs of energy, but also social and environmental costs, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, the lack of reliable information regarding financial costs, benefits, electricity output, incentive schemes, energy output, solar irradiation and potential environmental and societal benefits with respect to solar projects also act as hindrance for PV adoption. 13,53 In the context of PV prosumerism, Wuebben and Peters 58 in their research identified PV promoters barely focused on communicating environmental and societal benefits to consumers, which plays a pivotal role in public opinion shift.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The problem with subsidising renewables in Spain was described by Wuebben and Peters [41]. In 2008, Spain was the world leader in the number and output of photovoltaic installations.…”
Section: The Renewable Energy In Polandmentioning
confidence: 99%